MORAL SELF-IDENTIFICATION OF HIGH SCHOOL STUDENTS IN A CHANGING SOCIETY - Bocharova, E.E. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ psikhologii͡a︡ i pedagogika, 2017)
The paper presents the findings of an empirical study of moral self-identification conducted on a sample of senior high school students from Saratov (N = 142). The study demonstrates that high school students are not indifferent to other people’s moral evaluation of their actions. High school students’ perceptions of the importance of morality and ethics are associated with compulsory and mutual observance of moral standards and with their /manifested differentiation in the relation to «In- group» - “Others”, which confirms the dominance of their group-centric orientation. It was found that ethical behavior by implementing ethical standards in behavior, high school students have a sense of emotional satisfaction, adhering to the strategy of reciprocity. The study revealed a low severity of cognitive and conative components, which explains the weak differentiation of moral norms, the consequence of which is the difficulty in resolving moral problems. These findings can be applied in the development of the training programs aimed at developing an individual’s moral sphere, as well as preventive programs aimed at reducing the risk of destructive behavior in young people.